Metabolomic Profiling and Genomic Study of a Marine Sponge-Associated Streptomyces sp. - Viegelmann, C.; Margassery, L.; Kennedy, J.; Zhang, T.; O'Brien, C.; O'Gara, Fergal; Morrissey, J.; Dobson, A.; Edrada-Ebel, R. (M D P I AG, 2014)
Metabolomics and genomics are two complementary platforms for analyzing an organism as they provide information on the phenotype and genotype, respectively. These two techniques were applied in the dereplication and identification of bioactive compounds from a Streptomyces sp. (SM8) isolated from the sponge Haliclona simulans from Irish waters. Streptomyces strain SM8 extracts showed antibacterial and antifungal activity. NMR analysis of the active fractions proved that hydroxylated saturated fatty acids were the major components present in the antibacterial fractions. Antimycin compounds were initially putatively identified in the antifungal fractions using LC-Orbitrap. Their presence was later confirmed by comparison to a standard. Genomic analysis of Streptomyces sp. SM8 revealed the presence of multiple secondary metabolism gene clusters, including a gene cluster for the biosynthesis of the antifungal antimycin family of compounds. The antimycin gene cluster of Streptomyces sp. SM8 was inactivated by disruption of the antimycin biosynthesis gene antC. Extracts from this mutant strain showed loss of antimycin production and significantly less antifungal activity than the wild-type strain. Three butenolides, 4,10-dihydroxy-10-methyl-dodec-2-en-1,4-olide (1), 4,11-dihydroxy-10-methyl-dodec-2-en-1,4-olide (2), and 4-hydroxy-10-methyl-11-oxo-dodec-2-en-1,4-olide (3) that had previously been reported from marine Streptomyces species were also isolated from SM8. Comparison of the extracts of Streptomyces strain SM8 and its host sponge, H. simulans, using LC-Orbitrap revealed the presence of metabolites common to both extracts, providing direct evidence linking sponge metabolites to a specific microbial symbiont.